Characterization of Crystal Structures and Magnetic Properties of Polyethylene Glycol (PEG-4000) and Silica Encapsulated Mn0.5Zn0.5Fe2O4 Nanoparticles - Laisina, Edwin; Suharyadi, Edi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
In this research has been successfully Mn0.5Zn0.5Fe2O4 nanoparticles synthesis using co-precipitation method and their encapsulation by varying the concentration of polyethylene glycol (PEG-4000) and silica. The result of X-Ray Diffraction (XRD) characterization showed that Mn0.5Zn0.5Fe2O4 nanoparticles was mix spinel crystal structure. There was a phase other than Mn0.5Zn0.5Fe2O4 phase synthesized that a-Fe2O3 phase before and after encapsulated with PEG-4000 and silica. Encapsulation of silica has showed a new diffraction peak (222) because silica was crystal. Mn0.5Zn0.5Fe2O4 particle size before and after encapsulated with PEG-4000 (50% concentration) and silica (50% concentration) was 27.28±0.26 nm; 19.13±0.13 nm and 32.75±0.55 nm, respectively. The result of Transmission Electron Microscopy (TEM) characterization showed that before encapsulated with PEG-4000 and silica, occur agglomeration, meanwhile after encapsulated, the agglomeration was reduced. The result of Fourier Transform Infra Red (FTIR) characterization showed that Mn0.5Zn0.5Fe2O4 nanoparticles encapsulated with PEG-4000 there was shift in the wavenumbers 2878.00 cm-1 to 2885.51 cm-1 in the functional groups C-H and wavenumbers 1103.28 cm-1 to 1111.00 cm-1 in the functional groups C-O-C. Both of those functional groups was a constituent bond PEG-4000. Bonding metal oxide (M-O) was shift the wavenumbers 578.64 cm-1 to 570.93 cm-1, which was an uniform pattern of Mn0.5Zn0.5Fe2O4. Mn0.5Zn0.5Fe2O4 encapsulated with silica was shown in the wavenumbers 1049.28 cm-1; 779.24 cm-1; and 471.00 cm-1, which is the functional groups Si-O-Si (stretching). The characterization result of Mn0.5Zn0.5Fe2O4 magnetic properties with Vibrating Sample Magnetometer (VSM) showed that the values of coercivity, magnetization (at H = 15 kOe) and remnant magnetization was 47.55 Oe, 10.41 emu/g, 1.40 emu/g. After Mn0.5Zn0.5Fe2O4 nanoparticles encapsulated with PEG-4000 and silica was decreased amounting to 45.80 Oe, 45.64 Oe, 10.32 emu/g, 1.34 emu/g, 0.28 emu/g and 0.07 emu/g, respectively.